Osteopatía hipertrófica canina: Relato de caso - Borin, Sofía [UNESP]; Crivelenti, Leandro Zuccolotto [UNESP]; Ortiz, Edna M. Gómez [UNESP]; Ferreira, Fernando A. (My University, 2011)
A case of a 11 year old Boxer dog with hypertrophic osteopathy is presented. This is an uncommon pathological process characterized by bilaterally symmetric and generalized periosteal proliferative in long bones and falanges.
Canine hypertrophic osteopathy: Case report
Keywords: Bone; Canine; Lungs neoplasia; Periosteal proliferative; Canis familiaris